Electrophysiological Study in Patients with Cervical Radiculopathy (Iraqi Journal of Medical Sciences, 2024)
Background: Cervical radiculopathy is defined as a pathological process affecting the cervical nerve root(s). Electromyography (EMG), nerve conduction studies (NCS), and somatosensory evoked potentials (SEPs) are frequently used to evaluate spinal cord and nerve root function.Objective: To evaluate the sensitivity of different SEP components in detecting cervical nerve root lesions, as well as to test the NCS, and EMG, in patients with cervical radiculopathy.Methods: In this case control study, 41 patients with cervical radiculopathy and 40 healthy volunteers took part. Sensory and motor NCS of the ulnar and median nerves, EMG of the deltoid, biceps brachii, and abductor brevis, and SSEP of the median nerve were performed on each participant.Results: There was no difference in the motor and sensory NCS data between the study groups. The EMG of the muscles under investigation differed significantly between the two groups in terms of both duration and amplitude, with the exception of the abductor brevis muscle, which did not exhibit any differences. SEP data indicates that the patient's N9, N13, P14, and N20 latencies were all increased, as well as the patient's N13-N9, N20-N13, and N20-N9 interpeak latencies. The N13 and P14 latencies exhibited the highest sensitivity and specificity.Conclusion: SEPs are more sensitive in identifying mild posterior column dysfunction in patients with cervical radiculopathy, which is at least imperceptible on routine NCS. SEP testing is an essential adjunctive diagnostic method for evaluating the spinal cord and nerve roots electrophysiologically. The N13 and P14 components have the highest sensitivity and specificity when comparing the patient and control groups. Keywords: Cervical radiculopathy, NCS, EMG, SEPCitation: Kaddoori HG. Electrophysiological study in patients with cervical radiculopathy. Iraqi JMS. 2024; 22(1): 20-30. doi: 10.22578/IJMS.22.1.3
Keywords: Cervical radiculopathy; NCS; EMG; SEP